Establishing the Connection between Valency and Passive Voice in the English Simple Sentence Constructions - Yemisi Famakinwa; Bukola Alfred (CV. Rustam, 2024)
A sentence is generally construed as a unit which is made up of one or more clauses. Hence, the English simple sentence, made up of a subject and a predicate, contains just a clause which makes a complete thought and expresses a single proposition. Against this backdrop, this study examines the connection between valency and passive voice in the English simple sentence constructions. It further analyses samples of the English simple sentences both from the literature and introspection. As emanations from the English simple sentences, the English passive voice may be devoid of the ‘by-agentive’ phrase. The point just made does not rule out the presence of a predicate in such expressions. Noticeably, both the active and passive voice are connected to the English simple sentences. Employing the approach of Corpus Linguistics to sentence analyses, samples of the English simple sentences gathered from introspection and related literature are considered for analysis. The study re-affirms that there is a connection between valency and passive voice in the English simple sentence constructions. The study further discovers that the presence of referring expressions in both the active and passive voice sentence constructions indicates the number of valency in such constructions. The paper concludes by recommending that valency and passive voice in English grammar be painstakingly taught to both native and non-native learners of English since the former can be used to explain the latter and vice-versa.